English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I'm having trouble with math. Can somebody help me work this out?

Given f(x)= 5x+9 and g(x)= x squared + 8x Find (FoG)(2)

2006-12-08 09:07:55 · 7 answers · asked by texastreasure 3 in Science & Mathematics Mathematics

7 answers

FoG means
F(g(x))

So (FoG)(2)
=F(G(2))
=F(2^2+8*2)
=F(20)
=5*20+9
=109

2006-12-08 09:17:44 · answer #1 · answered by anonymous 3 · 0 0

To find f o g(x) substitute g(x) in for x in f(x).

f o g (x) = 5(x^2 + 8x) + 9
= 5x^2 + 40x + 9

f o g (2) = 5(2)^2 +40(2) + 9
= 5(4) + 80 + 9
= 20 + 80 + 9
= 109

2006-12-08 17:13:59 · answer #2 · answered by Jo G 1 · 0 0

f(x) = 5x + 9
g(x) = x^2 + 8x

To find (fog)(2), we have to first define what it means.

(fog)(2) = f(g(2))

So first, we solve for g(2).
g(2) = 2^2 + 8(2) = 4 + 16 = 20

Now, solve f(g(2))
f(g(2)) = f(20) = 5(20) + 9 = 100 + 9 = 109

2006-12-08 17:11:30 · answer #3 · answered by Puggy 7 · 0 0

You solve g(x) for x=2, then you solve f(x) for what you have obtained.

g(2)=2 squared + 8 times 2=20
f(20)=20 times 5 + 9= 109.

2006-12-08 17:12:57 · answer #4 · answered by Arc 2 · 0 0

f(x) = 5x + 9

g(x) = x

fog(2) = ?

1) fog(x) = f(g(x)) = f(x) = 5x + 9 => fog(2) = 5(2) + 9 = 19

2006-12-08 17:17:48 · answer #5 · answered by frank 7 · 0 1

first take G(2) which is 2squared + 8(2) which is 20

then take F(20) which is 5(20) + 9 = 109

This should be right.

2006-12-08 17:11:34 · answer #6 · answered by Mike 3 · 0 0

Substitute the f(x) for the "x" in the g(x) expression.
(F o G)(x) = f(g(x))

Plug and chug.

2006-12-08 17:17:27 · answer #7 · answered by Jerry P 6 · 0 0

fedest.com, questions and answers